Issues Management of Islamic Political Parties to Election Campaign in 2019 - Wuri Arenggoasih (Sunan Kalijaga: International Journal of Islamic Civilization, 2018)
In accordance with Article 29 of the 1945 Constitution of the Republic of Indonesia, Indonesia recognizes the religion and protects the freedom of the people in carrying out its religious teachings. Indonesia is a plural country because of the diversity of beliefs and the beliefs held by the community. But because of this diversity, Indonesia has a sensitivity especially associated with religious issues. In the last two years, the establishment of the negative issues about Islam has been increasing. Consequently, Islam is cornered in Indonesia. This situation is feared to be able to further exacerbate the potential for votes for the Islamic parties in the 2019 election. Therefore, the concept of issues management of Chase W. Howard model is used in this study to answer how the management of the Islamic party issues is to face the 2019 Election. The research method used is the qualitative descriptive approach in the interpretive paradigm with the design of case study research. The results of the research show that the Islamic party has exceeded all elements on the issues management of Chase model. These elements become the step of the Islamic party against the issues of Islam and exist in the democratic system, especially for the 2019 election without reducing the sense of peace in Indonesia.